Anti-glomerular Basement Membrane Glomerulonephritis: A Study in Real Life - Sánchez-Agesta, Marina; Rabasco, Cristina; Soler, María J.; Shabaka, Amir; Canllavi, Elisabeth; Fernández, Saulo J.; Cazorla, Juan M.; López-Rubio, Esperanza; Romera, Ana; Barroso, Sergio; Huerta, Ana; Calle, Leonardo; et al. (Frontiers in Medicine, 2022)
Introduction Anti-glomerular basement membrane (anti-GBM) disease is a severe entity with few therapeutic options that include plasma exchange and immunosuppressive agents. The aim of the study was to analyse the clinical and pathological features that predict evolution to end-stage kidney disease (ESKD) and the kidney survival in a cohort of anti-GBM patients with renal involvement in real life. Methods A retrospective multicentre observational study including 72 patients from 18 nephrology departments with biopsy-proven anti-GBM disease from 1999 to 2019 was performed. Progression to ESKD in relation to clinical and histological variables was evaluated. Results Creatinine at admission was 8.6(±4) mg/dL and 61 patients (84.7%) required dialysis. Sixty-five patients (90.3%) underwent plasma exchange. Twenty-two patients (30.6%) presented pulmonary haemorrhage. Kidney survival was worse in patients with creatinine levels >4.7 mg/dL (3% vs. 44% p < 0.01) and in patients with >50% crescents (6% vs. 49%; p = 0.03). Dialysis dependence at admission and creatinine levels >4.7 mg/dL remained independent significant predictors of ESKD in the multivariable analysis (HR [hazard ratio] 3.13 (1.25-7.84); HR 3 (1.01-9.14; p < 0.01). The discrimination value for a creatinine level >4.7 mg/dL and 50.5% crescents had an area under the curve (AUC) of 0.9 (95% CI 0.82–0.97; p < 0.001) and 0.77 (95% CI 0.56–0.98; p = 0.008), respectively. Kidney survival at 1 and 2 years was 13.5% and 11%, respectively. Patient survival at 5 years was 81%. Conclusions In real life patients with severe anti-GBM disease (creatinine >4.7 mg/dL and >50% crescents) remained with devastating renal prognosis despite plasma exchange and immunosuppressive treatment. New therapies for the treatment of this rare renal disease are urgently needed.